Tradisi Tilawah Al-Qur’an sebagai Penopang Identitas Muslim: Studi Ma’had Al-‘Ulum Addiniyyah Pohon Tanjong di Thailand Selatan - Topikurohman; R. Nanang Kuswara; Yasser Muda Lubis (Al-Ulum, 2025)
This study examines the role of Ma’had Al-‘Ulum Addiniyyah Pohon Tanjong in Southern Thailand in sustaining Muslim identity through the tradition of Qur’anic recitation. Using a qualitative fieldwork approach, data were collected through in-depth interviews, participant observation, and documentation involving teachers, leaders, and community figures. The findings show that the Ma’had plays a strategic role in preserving Qur’anic recitation by implementing formal education, tahfiz programs, recitation training, competitions, and collective tadarus. These efforts strengthen religious identity, enhance spiritual awareness, and ensure the continuity of Islamic tradition amid modernization and globalization.